2020
DOI: 10.1101/2020.07.13.20148668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the impacts of human mobility restriction on the spread of COVID-19: an empirical analysis from 344 cities of China

Abstract: Objective Since the outbreak of novel coronavirus pneumonia (COVID-19), human mobility restriction measures have raised controversies, partly due to inconsistent findings. Empirical study is urgently needed to reliably assess the causal effects of mobility restriction. Methods Our study applied the difference-in-difference (DID) model to assess declines of population mobility at the city level, and used the log-log regression model to examine the effects of population mobility declines on the disease spread me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Indeed, the reduction has affected the economy. However, analysis at the provincial level showed that the self-sufficient and self-sustainable economic regions, with internal supplies, production, and consumption, have recovered faster than those regions relying on global supply chains (Tan et al, 2020).…”
Section: Previous Studymentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, the reduction has affected the economy. However, analysis at the provincial level showed that the self-sufficient and self-sustainable economic regions, with internal supplies, production, and consumption, have recovered faster than those regions relying on global supply chains (Tan et al, 2020).…”
Section: Previous Studymentioning
confidence: 98%
“…The travel industry is dealing with an unprecedented wave of cancellations and a significant drop in demand amid strict governmental instructions to implement social distancing and the restriction of unnecessary travel . The situation has affected on travel-dependent industries, such as hotels, educational institutions and public transport, while the sectors that are mandatory for human life, such as offices, residential areas, restaurants and shopping malls, are recovering rapidly (Tan et al, 2020) COVID-19 is a disease which has affected most, if not all, countries in the world. The magnitude of the effect of Covid-19 has varied across countries.…”
Section: Previous Studymentioning
confidence: 99%